2012
DOI: 10.1002/macp.201200264
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant‐Dependent REDOX Responsiveness of Polysulfides

Abstract: Poly(propylene sulfide) (PPS) is studied as an oxidation‐responsive macromolecular building block, in the perspective of anti‐inflammatory therapies. Here, we show that the nature of the oxidant has profound effects on the outcome of the oxidation process. PPS was exposed to hydrogen peroxide (H2O2) and hypochlorite (OCl−), which are oxidizing species commonly encountered during inflammatory processes. It was found that the oxidation with H2O2 converted thioethers into sulfoxides, producing water‐soluble macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 48 publications
5
56
0
1
Order By: Relevance
“…Analogous results were reported by Tirelli and co-workers for oxidation of poly(propylene sulfide). 11 The changes in polarity from a nonpolar thioether to polar sulfoxide or sulfone units strongly influences the glass transition temperature. While mPEG 113 -b-PMTEGE 26 shows a T g of -61 °C, the emerging dipole-dipole interactions cause a T g of -33 °C for the sulfoxide In particular, we were interested in the behavior of mPEG-b-PMTEGE block copolymers in aqueous solution with H 2 O 2 treatment to investigate their potential as oxidation-responsive nanocarriers.…”
Section: Experimental Partmentioning
confidence: 99%
See 1 more Smart Citation
“…Analogous results were reported by Tirelli and co-workers for oxidation of poly(propylene sulfide). 11 The changes in polarity from a nonpolar thioether to polar sulfoxide or sulfone units strongly influences the glass transition temperature. While mPEG 113 -b-PMTEGE 26 shows a T g of -61 °C, the emerging dipole-dipole interactions cause a T g of -33 °C for the sulfoxide In particular, we were interested in the behavior of mPEG-b-PMTEGE block copolymers in aqueous solution with H 2 O 2 treatment to investigate their potential as oxidation-responsive nanocarriers.…”
Section: Experimental Partmentioning
confidence: 99%
“…This remarkable work inspired the design of various oxidation-responsive nanocarriers based on thioether-functional polymers. [8][9][10][11][12][13][14][15][16][17][18][19] Additionally, the nucleophilicity of sulfides allows for sulfonium salt formation with alkyl halides, similar to the quaternization of amines. Deming and co-workers demonstrated the suitability of thioether moieties as precursors for a variety of stable, water-soluble and highly functional polypeptide sulfonium derivatives, by click-type "quaternization" of poly(L-methionine).…”
Section: Introductionmentioning
confidence: 98%
“…Despite their potent ROS scavenging abilities and negligible cytotoxicity, [25,26,31,32] PPS-NPs have not yet been tested in the context of ischemic stroke, although PPS-derived microspheres have recently shown promise in a mouse model of hind leg ischemia. Despite their potent ROS scavenging abilities and negligible cytotoxicity, [25,26,31,32] PPS-NPs have not yet been tested in the context of ischemic stroke, although PPS-derived microspheres have recently shown promise in a mouse model of hind leg ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…Upon oxidation with H 2 O 2 , the initially hydrophobic PPS were converted to hydrophilic poly(propylene sulfoxide) and poly(propylene sulfone), leading to destabilization and dissociation of the polymersomes. Interestingly, recent results indicated that the oxidation kinetics and the oxidized products of PPS were highly dependent on the applied oxidants, that is, HOCl oxidized sulfides much faster than H 2 O 2 with the direct formation of sulfone groups, whereas oxidation by H 2 O 2 mainly produced sulfoxides (Figure ) …”
Section: Ronss‐responsive Polymersomesmentioning
confidence: 99%
“…Interestingly, recent results indicated that the oxidation kinetics and the oxidized products of PPS were highly dependent on the applied oxidants, that is, HOCl oxidized sulfides much faster than H 2 O 2 with the direct formation of sulfone groups, whereas oxidation by H 2 O 2 mainly produced sulfoxides ( Figure 1). [71] The encapsulation and entrapment of enzymes into the aqueous lumen of polymersomes has attracted broad interest for potential application in biomimetic organelles, [72] nanoreactors, [73] and enzyme-directed prodrug therapy. [74] It is well known that many oxidases (e.g., glucose oxidase, GOx, and xanthine oxidase, XO) catalyze production of H 2 O 2 under an aerobic condition.…”
Section: Thioether Oxidationmentioning
confidence: 99%